EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI PADI SAWAH DI KELURAHAN TONDANGOW KECAMATAN TOMOHON SELATAN - Dianne J.F. Pongoh; Esry O.H. Laoh; Gene H.M. Kapantow; Celsius Talumingan (COCOS, 2014)
ABSTRACTDianne Jilly Fioline Pongoh. Efficiency Use Of Production Factor in Rice Farming in Tondangow Village South Tomohon Sub District. Under the guidance of Esry O. H. Laoh as Chairman; Gene H. M. Kapantow and Celsius Talumingan as a Members.The objective of this research is to analyze the efficiency of production factors in rice farming. This study was conducted from November 2013 until January 2014. Primary and secondary data were used in this research. The primary data were obtained directly from respondents by using questionnaires. The secondary data were obtained from related institutions. Respondents were selected by using Simple Random Sampling method. The total samples are 20 members of rice farmers. Data were analyzed using the multiple regression analysis based on the Cobb Douglas model.The analysis showed that technically, the use of urea, phonska, and pesticides were efficient, whereas the use of labor has not efficient yet and the use of seeds has not efficient anymore. Allocatively, the use of urea, phonska and labor has not efficient yet, whereas the use of seeds and pesticides has not efficient anymore. Economically, all product factor analysis in this study (seeds, urea, phonska, pesticides and labor) weren’t efficient yet.